Boosting the Capacitance of Covalent Organic Framework Supercapacitors by Hydroquinone Redox Electrolyte Addition - Laura Sierra; Jesús Á. Martín-Illán; Félix Zamora; Pilar Ocón (Gels)
Rapidly escalating energy demands have spurred a relentless quest for innovative materials and methodologies in energy storage technologies. Covalent organic frameworks (COFs) have emerged as promising candidates for energy storage applications owing to their customizable structure and inherent properties, including enduring porosity and expansive surface area. In this study, we introduce imine-based COF aerogels fashioned into flexible COF electrodes, employing redox electrolytes based on hydroquinone (HQ) dissolved in H2SO4 aqueous solution and 0.25 M TBAPF6 at concentration in acetonitrile. This strategic selection of electrolytes aims to augment capacitance and energy density when compared to non-redox electrolytes. Remarkably, our COF electrodes exhibit an outstanding areal capacitance of 843 mF cm−2 when utilizing HQ with 0.10 M H2SO4, operating at 1.3 mA cm−2, while maintaining approximately 100% capacity retention after 10,000 cycles. Notably, the capacitance of the 0.38 M HQ + 0.10 M H2SO4 is eight times greater than that achieved with organic electrolytes (111 mF cm−2).